Tingkat Pengetahuan Siswi SMK Sentra Medika Medan tentang Premenstruasi Syndrome (PSM) - Salbiah Salbiah; Dina Indarsita; Novi Tesalonika Hutahaean (Jurnal Keperawatan, 2018)
Premenstrual syndrome (PMS) is one of the most common disorders in women. Severe symptoms of PMS can cause absenteeism at school or at work. Improving your lifestyle by increasing physical activity and a healthy diet can reduce the occurrence of PMS. The purpose of this study was to determine the level of knowledge of Medan Vocational High School students about PMS. Research was conducted from January to July 2017. The number of research samples was 86 people. Sampling was done in Accidental Sampling. Data is obtained by filling out questionnaires and descriptive research methods. The results of the study found that most of the respondents' level of knowledge was good at 64.0%, the source of information about 50% PMS came from health workers. 76% of female students have good knowledge about preventive measures against PMS. The results of the study show that with good knowledge, the PMS problem can be overcome